Implementation Of Patient Safety Culture By Nurses - Sri Rahayu Saragi; Balqis Wasliati; Ika Nur Saputri (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Patient safety in hospitals involves the participation of all health workers, especially nurses. Not only implemented by nurses, but also support from all parties involved either directly or indirectly towards the patient. Objective: This study aims to describe the implementation of patient safety culture at Wira Husada General Hospital. Research method: The research method uses qualitative descriptive. The subjects in the study consisted of main informants and triangulation informants. The main informant is 1 person from the hospital management, 5 technical implementers in the implementation of patient safety (IT 1-5). Then the triangulation informants are 3 patients (IT 6-8). Research results: Efforts made in the implementation of patient safety culture Based on Patient Identification at Wira Husada General Hospital have been running well. The implementation of a program policy will run smoothly when supported by the availability of resources, both human resources, facilities and financial resources (funds). However, on the contrary, if there is a lack of resources in a program policy, its implementation will tend to be ineffective. Conclusion: Efforts made in implementing patient safety culture Based on Effective Communication at Wira Husada General Hospital have been implemented well, the safety of High Alert drugs, based on the risk of infection, based on the risk of patient falls at Wira Husada General Hospital has been implemented well. Therefore, improvements are still needed from the Hospital to be able to optimize resources in services, especially human resources.